Relationship between nutritional status and menstrual cycle in medical student of Tarumanagara University - Fahmi Rachmatullah; Olivia Charissa (Science Midwifery, 2023)
The prevalence of women with menstrual cycle disorders is around 45% based on a statement from the World Health Organization (WHO) in 2012. Several factors affect the menstrual cycle including nutritional consumption, hormonal drugs, smoking, stress, endocrine disorders, and nutritional status. This study aims to determine the relationship between nutritional status and menstrual cycle in medical students of Tarumanagara University. This study was conducted on 161 respondents using a cross-sectional research design. Data was collected by distributing questionnaires through Google Forms and then tested using the chi-square test method. The results showed no significant relationship between undernutrition status and menstrual cycle with a p-value of 0.219. The results of this study found a non-meaningful relationship between over-nutrition status and menstrual cycle with a p-value of 0.427. In this study, it was found that there was no significant relationship between nutritional status either less or more with the menstrual cycle in female students of the Faculty of Medicine, Tarumanagara University.